1997
DOI: 10.1097/00005768-199711000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical activity and diet on lipoprotein(a)

Abstract: Lipoprotein(a) [Lp(a)] represents a class of lipoproteins with some structural similarity to low density lipoprotein (LDL), but containing a unique apoprotein, apoprotein(a). First reported in 1963, Lp(a) is now considered to have an independent role in the development of atherosclerotic lesions. The level of Lp(a) in the blood is under strong genetic influence and does not appear to be alterable by lifestyle factors known to influence other lipoproteins. Regular moderate exercise has been shown to favorably a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 55 publications
0
31
0
3
Order By: Relevance
“…At present, knowledge from cross-sectional as well as intervention studies does not suggest that plasma Lp(a) concentrations are significantly altered by physical activities or diet modifications recommended for health improvements [41][42][43]. This is in good agreement with our finding of only a negligible variation between pre-and postintervention Lp(a) values in the total group; neither caloric restriction and weight changes nor the nutrient quality showed any influence on the Lp(a) concentrations in the patients investigated.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…At present, knowledge from cross-sectional as well as intervention studies does not suggest that plasma Lp(a) concentrations are significantly altered by physical activities or diet modifications recommended for health improvements [41][42][43]. This is in good agreement with our finding of only a negligible variation between pre-and postintervention Lp(a) values in the total group; neither caloric restriction and weight changes nor the nutrient quality showed any influence on the Lp(a) concentrations in the patients investigated.…”
Section: Discussionmentioning
confidence: 89%
“…Regarding the effects of exercise, weight loss, and diet modifications on cholesterol and lipoproteins, a small remark has to be made on the effect of lifestyle management of Lp(a) [41]. At present, knowledge from cross-sectional as well as intervention studies does not suggest that plasma Lp(a) concentrations are significantly altered by physical activities or diet modifications recommended for health improvements [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Several population and cross-sectional studies showed a lack of association between serum Lp(a) levels and regular moderate physical activity or moderate exercise training. [20][21][22][23][24]29 The few studies that found a beneficial effect of exercise on Lp(a) were either confounded by ethnical issues 25 or included only men. 26 Therefore, it appears likely that the changes in Lp(a) levels observed in our study were caused by the dietary intervention rather than by the increased physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Similarly, the effect of physical exercise on Lp(a) levels is not fully understood, with several contradicting reports. [20][21][22][23][24][25][26][27][28][29] Only few studies were performed in children. 27,28 In this study, we therefore tested the possibility of lowering Lp(a) levels by a weight reduction program during a 3-week dietary camp for obese children.…”
Section: Introductionmentioning
confidence: 99%
“…two-fold relative risk of coronary atherosclerosis [3] rising to the range of five-fold when LDL and Lp(a) are both elevated [4] reduction of plasma Lp(a) concentration is recommended. Dietary interventions do not seem to be effective in lowering Lp(a) plasma levels [9,83] or even lead to an increase of Lp(a) in plasma, alone [84] or at least when combined with exercise 85]. The same phenomenon could be observed in case of exercise where cross-sectional data suggest that a lifestyle of moderate to intense exercise training does not exert a significant impact on the Lp(a) level [86,87].…”
Section: Lp(a) and Lipid Lowering Drugsmentioning
confidence: 99%